Exceptional Scarp Preservation in SW Namibia Reveals Geological Controls on Large Magnitude Intraplate Seismicity in Southern Africa. Issue 4 (29th March 2023) - Muir, R. A.; Whitehead, B. A.; New, T.; Stevens, V.; Macey, P. H.; Groenewald, C. A.; Salomon, G.; Kahle, B.; Hollingsworth, J.; Sloan, R. A.
Abstract: Four previously unrecognized neotectonic fault scarps in southwest Namibia are described. These relatively straight, simple but segmented structures are 16–80 km long and have measured vertical separations of 0.7–10.2 m. We estimate that each is capable of producing earthquakes of M w 6.4 or greater, indicating that large earthquakes may occur despite limited cumulative displacement. There is strong evidence that some of these scarps were formed by repeated earthquakes. Comparison with aeromagnetic and geological maps reveal that the normal faults reactivate major crustal weaknesses that are orientated north‐south and northwest‐southeast and perpendicular to the local gravitational potential energy gradient. The presence of these structures in an area with a limited record of instrumental seismicity suggests that the M max of this region may be much larger than generally assumed. They highlight the necessity of incorporating information from fault studies into probabilistic seismic hazard assessments in this region, in a similar way to other stable continental regions such as Australia. The fact that such major structures have gone hitherto unrecorded suggests significant further research is needed to characterize these sources of hazard. The identification of an apparent cluster of large magnitude neotectonic earthquakes in the area may be related to the exceptional preservation potential of scarps rather than indicating an area of comparatively rapid deformation. If this interpretation is correct, then these scarps represent an important indication of the potential seismic hazard across the region, and the occurrence of infrequent large‐magnitude seismicity on similar structures should be considered throughout southwestern Africa. Plain Language Summary: Namibia is considered to be a region that has very few large earthquakes. This is partly because previously evidence has not been found in the landscape to suggest that many large earthquakes have occurred in the past. However, in this study we show evidence in SW Namibia of four previously unidentified but significant fault scarps (steps in the landscape generated by movement during earthquakes). These features indicate that significant earthquakes can and have occurred in southern Namibia in the geologically recent past. We also find evidence for repeated motion along these faults and therefore repeated earthquake generation. The extremely dry climate and abundance of hard, well‐cemented sediments in the Namib Desert makes it one of the best places in the world for preserving fault scarps. This means we can get a much better idea of the type of earthquakes which could occur over relatively long timescales, and we find evidence for much larger events than would previously have been expected in this area. It is important to consider these features in earthquake hazard assessments in southwestern Africa and other similar areas around the world. Key Points: Four major neotectonic normal faults are identified in a small area of SW Namibia Scarps show evidence of repeated brittle reactivation of ancient ductile structures in large earthquakes Exceptional preservation may be responsible for the unexpected density of observable paleoseismic ruptures in the area